Emerging New-Generation Semiconductor Single Crystals of Metal Halide Perovskites for Radiation Detection - Guigen Luo; Min Peng; Zhibin Yang; Chungming Paul Chu; Zhengtao Deng (Inorganics)
Radiation detection uses semiconductor materials to convert high-energy photons into charge (direct detection) or low-energy photons (indirect detection), and it has a wide range of applications in nuclear physics, medical imaging, astronomical detection, homeland security, and other fields. Metal halide perovskites have the advantages of high frequency number, high carrier mobility, high defect tolerance, low defect density, adjustable band gap, and fast light response, and they have wide application prospects in the field of radiation detection. However, the research is still in its infancy stage, and it is far from meeting the requirements of industrial application. This paper focuses on the advantages of metal halide perovskite single-crystal materials in both semiconductors-based direct conversion detection and scintillator-based indirect detection as well as the latest progress in this promising field. This paper not only introduces the latest application of lead halide perovskite monocrystalline materials in high-energy electromagnetic radiation detection (X-ray and γ-rays), but it also introduces the latest development of α-particle/β-particle/neutron detection. Finally, this paper points out the challenges and future prospects of metal halide perovskite single-crystal materials in radiation detection.